![( \frac{ - 3}{2} ) {}^{ - 1} = ( \frac{ - 3}{2} ) {}^{ - 1} =](https://tex.z-dn.net/?f=%28+%5Cfrac%7B+-+3%7D%7B2%7D+%29+%7B%7D%5E%7B+-+1%7D++%3D+)
![( \sqrt{ {7}^{} } ) {}^{3} = ( \sqrt{ {7}^{} } ) {}^{3} =](https://tex.z-dn.net/?f=%28+%5Csqrt%7B+%7B7%7D%5E%7B%7D+%7D+%29+%7B%7D%5E%7B3%7D++%3D+)
![{5}^{ \frac{2}{7} } = {5}^{ \frac{2}{7} } =](https://tex.z-dn.net/?f=+%7B5%7D%5E%7B+%5Cfrac%7B2%7D%7B7%7D+%7D++%3D+)
alguém poderia me ajudar ?
Soluções para a tarefa
Respondido por
2
Resposta:
a)
(-3/2)⁻¹ =(-2/3)¹ =-2/3
b)
(√7)³=[7^(1/2)]³ = 7^(3/2)
ou também pode ser
(√7)³= √7 * √7 * √7 = √7² * √7=7√7
c)
5^(2/7)=(5²)^(1/7) =[5^(1/7)]²
Perguntas interessantes
Geografia,
9 meses atrás
Saúde,
9 meses atrás
Matemática,
9 meses atrás
Física,
11 meses atrás
História,
11 meses atrás
Matemática,
1 ano atrás